Edukasi Fostering Safe and Supportive Learning Environments through Anti Bullying Education in Islamic Boarding Schools - Hosen Hosen (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service research aims to provide anti-bullying education to create a safe and comfortable learning environment for students at the Matlabul Ulum Jambu Lenteng Islamic Boarding School in Sumenep. Bullying, whether physical, verbal, or psychological, has been shown to negatively impact students' mental health, social well-being, and learning motivation. The research used a qualitative, participatory approach through observation, interviews, and educational activities involving students, religious teachers and boarding school administrators. The educational program was implemented through religious lectures, group discussions, role-playing, and the reinforcement of Islamic values such as brotherhood, empathy, and mutual respect. The results showed a significant increase in students' awareness of the dangers of bullying, a decrease in bullying cases, and increased empathy and social awareness among students. The active role of the teachers and boarding school administrators, along with the implementation of a stricter monitoring system, contributed to the program's success. Overall, the anti-bullying education at this Islamic boarding school was effective in building a more peaceful, inclusive, and character-based culture. Going forward, this program needs to be continuously evaluated and strengthened so that anti-bullying values become more ingrained in the students' daily lives.